Axitinib eutectic crystal and preparation method thereof
Through eutectic technology, the prepared axitinib-fumaric acid-acetic acid eutectic solves the photosensitivity and insolubleness of axitinib, significantly improves its stability, solubility and bioavailability, and is suitable for industrialized drug production.
Patent Information
- Application Number
- CN202411278782.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Due to its photosensitivity and insolubleness, it is difficult to achieve significant improvements in bioavailability, stability and manufacturability in the prior art.
Using eutectic technology, a kind of axitinib-fumaric acid-acetic acid eutectic is prepared. Through specific solvents and process conditions, a basic crystal unit consisting of axitinib, a molecule of fumaric acid, and a molecule of acetic acid is formed.
This eutectic has achieved great improvements in stability, solubility, permeability, etc., and has performed well in light stability. It is suitable for industrial production and large-scale promotion and application.
Smart Images

Figure BDA0005041014100000011 
Figure BDA0005041014100000041 
Figure BDA0005041014100000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crystalline drug molecules, and in particular to a preparation method and application of an axitinib-fumaric acid-acetic acid cocrystal. Background Art
[0002] Axitinib is a potent and selective inhibitor of vascular endothelial growth factor receptor (VEGFR) / platelet-derived growth factor (PDGFR) receptor tyrosine kinase (RTK) developed by Pfizer, USA, for inhibiting early to late stage cancer. It was approved for marketing by the US FDA on January 27, 2012, with the trade name of On April 29, 2015, Axitinib was approved by CFDA for use in adult patients with advanced renal cell carcinoma (RCC) who have failed treatment with a tyrosine kinase inhibitor or cytokine. Its chemical name is: N-methyl-2-[3-((E)-2-pyridin-2-yl-vinyl)-1H-indol-6-ylsulfonyl]-benzamide, and its structural formula is as follows:
[0003]
[0004] Due to the many problems of photosensitivity and poor solubility of axitinib itself, people in this field are trying to develop different crystal forms to obtain axitinib crystal forms that are more suitable for pharmaceutical use. Patent WO2006048751A1 attempts to study axitinib crystal forms, and discloses axitinib crystal forms I, II, III, IV, VI, VII and VIII, but simply changing the axitinib crystal form does not significantly improve its solubility. For example, the solubility of crystal form IV in an aqueous solution with a pH of about 1 is about 0.55 mg / ml, in an aqueous solution with a pH of about 2, the solubility is only 0.157 mg / ml, and in an aqueous solution with a pH of about 6.5, the solubility is only 2 μg / ml; at the same time, it is reported that in order to improve the water solubility of axitinib, 7 axitinib acid salt compounds were prepared, and their solubility was improved, but they were significantly degraded when exposed to high-intensity light, and all of them were photosensitive axitinib salts. Patent CN200880016453.6 discloses multiple crystal forms including crystal form XXV, crystal form XVI, crystal form XLI, crystal form IX, crystal form XII and crystal form XV. Crystal form XXV and crystal form XLI have not been significantly improved in terms of solubility and bioavailability.
[0005] Due to the many problems of photosensitivity and poor solubility of axitinib itself, people in this field are trying to develop different crystal forms to obtain axitinib crystal forms that are more suitable for pharmaceutical use. However, according to current reports, from the perspective of bioavailability, stability and manufacturability, among the many publicly available axitinib crystal forms, only crystal form IV and crystal form XLI are available. Due to the extreme instability of crystal form IV under light exposure, the original Pfizer company finally selected crystal form XLI with relatively less light exposure degradation as the marketed crystal form (see CHMP evaluation report). However, those skilled in the art know from the report of patent CN200880016453.6 that the potency of marketed crystal form XLI after light exposure is reduced to 89%. In order to achieve pharmaceutical safety and effectiveness, the preparation process using the light shielding process is still inevitable. However, some subsequent developments and studies of axitinib solvate crystal forms, axitinib salt crystal forms, and axitinib new crystal forms still have defects in drug safety, solubility, bioavailability or photostability.
[0006] For example, patent WO2015067224A1 further characterized 7 axitinib acid salts by powder diffraction data based on the 7 available axitinib acid salt compounds disclosed in patent WO2006048751A1. Patent CN201510509413.7 discloses the preparation of a crystalline form A of axitinib fumarate, in which the molar ratio of axitinib to fumaric acid is 1:1. After irradiation with light, axitinib fumarate degraded by 0.13%. CN202010787156.4 discloses a crystalline form B of axitinib fumarate, in which the molar ratio of axitinib to fumaric acid is 1:1.5; the axitinib fumarate crystalline form B powder sample was irradiated for 10 days, and the appearance and drug content did not change significantly. However, the water adsorption rate was 1.5% at 95% RH. CN202011575325.4 provides a maleate crystalline form of axitinib, wherein the molar ratio of axitinib to maleic acid in the maleate crystalline form is 1:1, and two molecules of axitinib, two molecules of maleic acid, and two molecules of water constitute the basic unit of the crystalline form. Beneficial effects have been achieved in terms of stability, solubility, and permeability.
[0007] According to statistics, in the process of drug development, more than 40% of candidate drugs have poor water solubility, poor permeability, and low bioavailability, which makes some candidate drugs with potential clinical value unable to enter clinical research; for these poorly soluble drugs, the use of cocrystal technology to solve the problem of poor drug solubility has attracted particular attention in recent years. Drug cocrystals are an important form of multi-component drug crystals, which refers to the crystals formed by the drug (API) and the pharmaceutically acceptable small molecule ligand copolymer (CCF) that is solid at room temperature through hydrogen bonds, van der Waals forces, π-π stacking, halogen bonds and other non-covalent bonds in a fixed stoichiometric ratio. Cocrystal technology is a new technology that can improve the physical and chemical properties of drug molecules, such as stability, solubility, permeability and bioavailability, and improve their drugability without changing the molecular structure of the drug. For example, the bioavailability of the flavonoid compound quercetin prepared into cocrystals with caffeine, theobromine, and isonicotinamide has been increased by 2.5 to 10 times.
[0008] In order to better utilize axitinib and fumaric acid or maleic acid crystal forms in drug synergistic therapy, the present invention provides a simple and easy-to-operate method for preparing high-purity axitinib-fumaric acid-acetic acid cocrystal form, thereby more efficiently utilizing the medicinal value of axitinib. Summary of the invention
[0009] In view of the deficiencies in the prior art, an object of the present invention is to provide an axitinib-fumaric acid-acetic acid cocrystal; the cocrystal has definite main crystallographic parameters and atomic spatial positions; and has achieved significant improvements in stability, solubility, permeability, etc.
[0010] The specific technical contents of the present invention are as follows:
[0011] In a first aspect, the present invention provides an axitinib-fumaric acid-acetic acid co-crystal, in which one molecule of axitinib, one molecule of fumaric acid, and one molecule of acetic acid constitute a basic unit of the crystal form.
[0012] Preferably, the axitinib-fumaric acid-acetic acid cocrystal, using Cu-Kα radiation, has an X-ray diffraction spectrum expressed in 2θ with characteristic peaks at 23.06±0.2°, 25.80±0.2°, 29.04±0.2°, 29.67±0.2°, 38.21±0.2°, and 38.89±0.2°.
[0013] Preferably, the axitinib-fumaric acid-acetic acid cocrystal uses Cu-Kα radiation, and the X-ray diffraction spectrum expressed in 2θ has characteristic peaks at 7.08±0.2°, 14.65±0.2°, 16.23±0.2°, 18.25±0.2°, 20.97±0.2°, 23.06±0.2°, 24.97±0.2°, 25.80±0.2°, 27.04±0.2°, 29.04±0.2°, 29.67±0.2°, 38.21±0.2°, and 38.89±0.2°.
[0014] Preferably, the axitinib-fumaric acid-acetic acid cocrystal, using Cu-Kα radiation, has a characteristic peak that meets Figure 1 And the X-ray powder diffraction pattern and detection data shown in Table 1.
[0015] Preferably, the crystallographic parameters of the axitinib-fumaric acid-acetic acid cocrystal are: triclinic system, chiral space group is P-1; unit cell parameters are: α=82.210(2)°,β=75.602(2)°,γ=86.744(2)°,unit cell volume
[0016] Preferably, the axitinib-fumaric acid-acetic acid cocrystal has two endothermic peaks in the differential scanning calorimetry (DSC) curve, which are 143.96° C. and 211.81° C. respectively.
[0017] The second aspect of the present application provides a method for preparing axitinib-fumaric acid-acetic acid cocrystal, and the specific preparation steps include: dissolving axitinib and fumaric acid in solvent A, heating to dissolve to obtain a transparent solution, cooling and standing to crystallize, filtering, washing, and vacuum drying to obtain axitinib-fumaric acid-acetic acid cocrystal.
[0018] Preferably, the solvent A is a mixed solvent of an organic solvent and acetic acid, wherein the organic solvent is one or two of methanol, ethanol, acetone, and isopropanol. The solvent A is further preferably selected from a mixed solvent of acetic acid-methanol, acetic acid-ethanol, acetic acid-acetone, and acetic acid-isopropanol.
[0019] Preferably, the volume ratio of the organic solvent to acetic acid in the solvent A is 1 to 5:1.
[0020] Preferably, the molar ratio of axitinib to fumaric acid is 1:1.00 to 1.40; further preferably, the molar ratio of axitinib to fumaric acid is 1:1.00 to 1.2.
[0021] Preferably, the mass-to-volume ratio of axitinib to solvent A is 3-8:1, wherein the mass is measured in mg and the volume is measured in mL.
[0022] Preferably, the dissolving and heating temperature is 60-75°C.
[0023] Preferably, the cooling and crystallization temperature is 10-30°C, and more preferably, the cooling and crystallization temperature is 10-25°C.
[0024] Preferably, the crystallization time is 36 to 48 hours.
[0025] Preferably, the drying temperature is 60-65° C., and the drying time is 5-9 hours.
[0026] Preferably, the solvent for washing the filter cake is selected from one of methanol, ethanol, acetone and n-butanol.
[0027] The third aspect of the present invention provides a pharmaceutical composition comprising the axitinib-fumaric acid-acetic acid cocrystal prepared as described above, mixed with other components.
[0028] Preferably, the pharmaceutical composition of the present invention is prepared by combining the compound of the present invention with a pharmaceutically acceptable solid or liquid carrier and optionally with a pharmaceutically acceptable excipient to prepare a usable dosage form using standard and conventional techniques.
[0029] Preferably, the other components include other active ingredients, fillers, diluents, binders, disintegrants, lubricants, etc. that can be used in combination.
[0030] Further preferably, the diluent is selected from one or more of starch, sucrose, dextrin, lactose, microcrystalline cellulose, mannitol, and sorbitol; the binder is selected from one or more of methylcellulose, hydroxypropyl cellulose, hydroxypropyl methylcellulose, sodium hydroxymethyl cellulose, ethyl cellulose, and povidone; the disintegrant is selected from one or more of sodium carboxymethyl starch, low-substituted hydroxypropyl cellulose, cross-linked sodium carboxymethyl cellulose, and cross-linked povidone; the lubricant is selected from one or more of magnesium stearate, micropowdered silica gel, talc, and sodium lauryl sulfate.
[0031] Preferably, the pharmaceutical composition is in the form of tablets, capsules, granules and pills.
[0032] The fourth aspect of the present application provides a use of axitinib-fumaric acid-acetic acid cocrystal as an active ingredient in the preparation of therapeutic anticancer drugs.
[0033] Confirmation of crystal structure
[0034] The X-ray powder diffraction test instrument and test conditions in the axitinib-fumaric acid-acetic acid cocrystal test of the present invention are: PANalytical Empyrean X-ray powder diffractometer; light source Cu target, flat sample stage, incident light path: BBHD, diffraction light path: PIXCEL, voltage 45KV, current 40mA, divergence slit of 1 / 4°, anti-scattering slit of 1°, Soller slit of 0.04rad, counting time of each step of 0.5s, scanning range of 3 to 50°. According to the crystallographic data, the characteristic peaks in the corresponding X-ray powder diffraction pattern (Cu-Kα) are detailed in the attached Figure 1 And Table 1.
[0035] Table 1 Main PXRD peaks of axitinib-fumaric acid-acetic acid cocrystal
[0036]
[0037]
[0038] X-ray crystallographic data were collected on a Rigaku XtaLAB Synergy instrument at 293(2)K using CuKa radiation, ω scanning mode, and Lp correction. The structure was solved by direct method, and all non-hydrogen atoms were found by difference Fourier method. All hydrogen atoms on carbon and nitrogen were obtained by theoretical hydrogenation, and the structure was refined by least square method.
[0039] The crystallographic data of the axitinib-fumaric acid-acetic acid cocrystal prepared by the present invention were tested and analyzed, and its crystallographic parameters were: triclinic system, chiral space group was P-1; unit cell parameters were: α=82.210(2)°,β=75.602(2)°,γ=86.744(2)°,unit cell volume Molecular formula: C 28 H 26 N4O7S, molecular weight: 562.59. The stacking diagram of the axitinib-fumaric acid-acetic acid eutectic of the present invention is shown in the attached Figure 2 The structural analysis ORTEP diagram of the axitinib-fumaric acid-acetic acid co-crystal of the present invention shows that the crystal contains one molecule of axitinib, one molecule of fumaric acid and one molecule of acetic acid, as shown in the attached Figure 3 shown.
[0040] Table 2 Main crystallographic data of axitinib-fumaric acid-acetic acid cocrystal
[0041]
[0042]
[0043] The TGA / DSC thermal analysis tester and test conditions in the present invention are as follows: TGA / DSC thermal analyzer: METTLER TOLEDO TGA / DSC3+; dynamic temperature section: 30-300°C; heating rate: 10°C / mIVn; program section gas N2; gas flow: 50mL / mIVn; crucible: aluminum crucible 40μl.
[0044] The TGA / DSC test results of the axitinib-fumaric acid-acetic acid cocrystal prepared by the method of the present invention are as follows: Figure 4 As shown, the DSC test results have two endothermic peaks, corresponding to temperatures of 143.96°C and 211.81°C, respectively. According to the TGA test results, it can be seen that there are two weight loss steps, and the first step indicates that the crystal contains one molecule of acetic acid. Combined with the DSC / TGA test results, it is shown that the crystal prepared by the present invention is axitinib-fumaric acid-acetic acid cocrystal crystal form.
[0045] All samples prepared in the examples have the same crystallographic parameters and X-ray powder diffraction spectra as described above.
[0046] The axitinib-fumaric acid-acetic acid cocrystal prepared by the present invention has achieved great improvements in stability, solubility, permeability, etc. After long-term photostability inspection, the cocrystal has good photostability. The axitinib-fumaric acid-acetic acid cocrystal has a regular crystal form, uniform particle size, clear crystallographic main parameters and exact atomic spatial positions, and a simple preparation method, which provides a material basis for improving the oral bioavailability of axitinib and is suitable for industrial production and large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 : X-ray powder diffraction pattern of axitinib-fumaric acid-acetic acid cocrystal.
[0048] Figure 2 : Stacking diagram of axitinib-fumaric acid-acetic acid cocrystal.
[0049] Figure 3 : ORTEP diagram of axitinib-fumaric acid-acetic acid cocrystal.
[0050] Figure 4 : DSC-TGA pattern of axitinib-fumaric acid-acetic acid cocrystal. DETAILED DESCRIPTION
[0051] The present invention is further illustrated by the following examples. It should be correctly understood that the examples of the present invention are only used to illustrate the present invention, rather than to limit the present invention. Therefore, simple improvements to the present invention based on the method of the present invention are all within the scope of protection claimed by the present invention.
[0052] Materials used in the experiment: Axitinib can be purchased or prepared according to the method disclosed in patent WO2006048745. The axitinib crystal form required for the comparative experiment can be prepared according to the existing technology or purchased; the materials used in other experiments without indicating the source and specification are all commercially available analytically pure or chemically pure.
[0053] Example 1
[0054] Add 482 mg of axitinib and 172 mg of fumaric acid to 20 mL of acetic acid and 60 mL of methanol, heat to 65°C, stir and dissolve, reflux for 4 hours, slowly cool to 10-25°C, control the temperature and let stand for crystallization for 36 hours, filter, wash the filter cake with methanol, and vacuum dry at 60°C for 6 hours to obtain axitinib-fumaric acid-acetic acid cocrystals with a yield of 98.01% and a purity of 99.75%.
[0055] Example 2
[0056] Add 404 mg of axitinib and 132 mg of fumaric acid to 20 mL of acetic acid and 70 mL of ethanol, heat to 65°C, stir to dissolve, reflux for 4 hours, slowly cool to 10-25°C, control the temperature and let stand for crystallization for 36 hours, filter, wash the filter cake with ethanol, and vacuum dry at 60°C for 6 hours to obtain axitinib-fumaric acid-acetic acid cocrystals with a yield of 98.51% and a purity of 99.71%.
[0057] Example 3
[0058] Add 397 mg of axitinib and 125 mg of fumaric acid to 15 mL of acetic acid and 60 mL of acetone, heat to 60°C, stir and dissolve, reflux for 4 hours, slowly cool to 10-25°C, control the temperature and let stand for crystallization for 36 hours, filter, wash the filter cake with acetone, and vacuum dry at 60°C for 6 hours to obtain axitinib-fumaric acid-acetic acid cocrystals with a yield of 95.11% and a purity of 99.68%.
[0059] Example 4
[0060] 461 mg of axitinib and 185 mg of fumaric acid were added to 20 mL of acetic acid and 70 mL of n-butanol, heated to 70°C and stirred to dissolve, refluxed for 4 hours, slowly cooled to 10-25°C, and then allowed to stand for crystallization for 36 hours under controlled temperature, filtered, and the filter cake was washed with n-butanol, and vacuum dried at 60°C for 6 hours to obtain axitinib-fumaric acid-acetic acid cocrystals with a yield of 94.88% and a purity of 99.73%.
[0061] Verification example:
[0062] The present invention investigates the above-prepared axitinib crystal form in terms of stability, hygroscopicity, solubility, permeability, etc. The specific implementation contents are as follows:
[0063] 1. Photostability test
[0064] The crystal form obtained in Example 1 was stored at 25°C (RH 45%) under strong light irradiation (4500 Lx±500 Lx), and samples were taken after 5 days and 10 days, and the purity was tested by HPLC. The results are shown in Table 3.
[0065] Table 3 Results of photostability test of axitinib crystals
[0066]
[0067] The results of the photostability test show that after 10 days under strong light irradiation, the axitinib-fumaric acid-acetic acid cocrystal prepared by the present invention has good photostability. It is found that Examples 1 to 4 have similar stability test results.
[0068] 2. Moisture absorption test
[0069] The co-crystal obtained in Example 1, the form B of axitinib fumarate in CN202010787156.4 (prepared by repeating Example 1), and the form of axitinib maleate in CN202011575325.4 (prepared by repeating Example 1) were taken for hygroscopicity test.
[0070] The hygroscopicity test method and conditions refer to the Chinese Pharmacopoeia 2020 Edition Part IV General Chapter 9103 Guiding Principles for Drug Hygroscopicity Test
[0071] Among them, the description of hygroscopic characteristics and the definition of hygroscopic weight gain are:
[0072] Deliquescent: Absorbs sufficient water to form a liquid.
[0073] Highly hygroscopic: weight gain due to moisture absorption is not less than 15%.
[0074] Hygroscopic: Weight gain due to moisture absorption is less than 15% but not less than 2%.
[0075] Slightly hygroscopic: weight gain due to moisture absorption is less than 2% but not less than 0.2%.
[0076] No or almost no hygroscopicity: weight gain due to moisture is less than 0.2%.
[0077] The results of the hygroscopicity test are shown in Table 4.
[0078] Table 4 Hygroscopicity investigation results
[0079]
[0080] Conclusion: The axitinib-fumaric acid-acetic acid cocrystal obtained by the present invention has no or almost no hygroscopicity, is not easily affected by high humidity and deliquesces, and is convenient for long-term storage of drugs. In addition, PXRD detection is performed on the crystal form after moisture absorption to test that each crystal form is stable and unchanged.
[0081] 3. Solubility test
[0082] Test method: Take water, 0.01 mol / L hydrochloric acid solution, and pH 6.8 PBS buffer as the medium, take an excess of the cocrystal obtained in Example 1, add it to the above medium, and stir at 37°C for 72 hours. Repeat the sampling three times, filter, take an appropriate amount of the filtrate, dilute, and use HPLC to detect the solubility in each medium.
[0083] Table 5 Solubility of Axitinib in different media (mg / ml)
[0084]
[0085] The solubility test results show that the solubility of the axitinib-fumaric acid-acetic acid cocrystal prepared by the present invention has been significantly improved compared with the available crystal forms disclosed in the prior art. It was found that Examples 1 to 4 have similar solubility test results.
[0086] 4. Permeability test
[0087] Test conditions: The permeability test was carried out using the Franz diffusion cell method at a water temperature of (37±0.5)℃.
[0088] Dialysis membrane (model: MW 14000Da, Himedia, India): treated with 10% sodium bicarbonate solution, 10 MmEDTA solution, and deionized water at 70 °C for 20 min respectively; the treated dialysis membrane was placed in a diffusion cell (effective surface area 4.15 cm 2 ); the donor chamber was respectively taken from Example 1 and CN202010787156.4, the crystal form B of axitinib fumarate (prepared by repeating Example 1) (based on the amount of axitinib, 10 mg) and suspended in 2 ml of distilled water; the receptor chamber was filled with phosphate buffer (pH = 7.4), maintained at room temperature, bubbles were removed, and magnetic stirring was performed at 45 ± 5 RPM; the cumulative permeation amount was tested after 24 hours.
[0089] Table 6 Cumulative permeation of axitinib (mg / cm 2 )
[0090] sample <![CDATA[Penetration cumulative amount (mg / cm 2 )]]> Example 1 0.5129 Axitinib fumarate crystal form B 0.1897
Claims
1. An axitinib cocrystal, characterized in that The molar ratio of axitinib, fumaric acid and acetic acid in the crystal unit structure is 1:1:
1.
2. The axitinib cocrystal according to claim 1, characterized in that Using Cu-Kα radiation, the X-ray diffraction spectrum expressed in 2θ has characteristic peaks at 23.06±0.2°, 25.80±0.2°, 29.04±0.2°, 29.67±0.2°, 38.21±0.2°, and 38.89±0.2°.
3. The axitinib cocrystal according to claim 1, characterized in that Using Cu-Kα radiation, the X-ray diffraction spectrum expressed in 2θ has characteristic peaks at 7.08±0.2°, 14.65±0.2°, 16.23±0.2°, 18.25±0.2°, 20.97±0.2°, 23.06±0.2°, 24.97±0.2°, 25.80±0.2°, 27.04±0.2°, 29.04±0.2°, 29.67±0.2°, 38.21±0.2°, and 38.89±0.2°.
4. The axitinib cocrystal according to claim 1, characterized in that Using Cu-Kα radiation, its characteristic peaks conform to the X-ray powder diffraction spectrum shown in FIG1 .
5. The axitinib cocrystal according to claim 1, characterized in that Its crystallographic parameters: triclinic system, chiral space group is P-1; unit cell parameters are: α=82.210(2)°,β=75.602(2)°,γ=86.744(2)°,unit cell volume 6. The method for preparing the axitinib cocrystal according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: dissolving axitinib and fumaric acid in solvent A, heating to dissolve to obtain a transparent solution, cooling and standing to crystallize, filtering, washing, and vacuum drying to obtain axitinib co-crystal.
7. The preparation method according to claim 6, characterized in that: The solvent A is a mixed solvent of an organic solvent and acetic acid, wherein the organic solvent is one or two of methanol, ethanol, acetone and isopropanol.
8. The preparation method according to claim 6, characterized in that: The molar ratio of axitinib to fumaric acid is 1:1.00-1.
40.
9. The preparation method according to claim 6, characterized in that The dissolving and heating temperature is 60-75°C; the cooling and crystallizing temperature is 10-30°C, preferably, the cooling and crystallizing temperature is 10-25°C.
10. Use of the axitinib co-crystal according to any one of claims 1 to 5 as an active ingredient in the preparation of anti-tumor drugs.
Citation Information
Patent Citations
Novel crystalline forms of a vegf-r inhibitor
CN101679356A
Axitinib fumarate, its crystalline form, and preparation method
CN106467512B
Axitinib maleate crystal form and preparation thereof
CN114685435A
Methods for preparing indazole compounds
WO2006048745A1
Polymorphic forms of 6-[2-(methylcarbamoyl)phenylsulfanyl]-3-e-[2-(pyridin-2-yl)ethenyl]indazole
WO2006048751A1